PENGARUH IMPLEMENTASI KEARSIPAN TERHADAP EFEKTIVITAS KINERJA PEGAWAI PADA KANTOR DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN TABANAN - Sari Dewi, Ni Luh Putu Diana; Supriliyani, Ni Wayan; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2016)
ABSTRACT The purpose of this research is to gain an overview of the actual manner implementation in archival influence on effectiveness of employee performance at the office population and civil registration Tabanan Regency. This study used quantitative research methods. The method of data collection used likert scale and questionnaire method. The instrument was tested use validity and reliability. The data technique used is descriptive analysis, classic assumpation test including normality testÂ  and heteroscedasticity test, to determine the effed of use simple linier regression. The results showed that the effective filling implementation and have a significant positive influence of the effectiveness of employee performance at the office population and civil registration Tabanan Regency. Keyword :Â  Archives, Employee Performance Effectiveness